Risk Factors for Cervical Cancer in Ghana - Nartey, Y.; Amo-Antwi, K.; Dassah, E.T.; et al. (Cancer Reports, 2024)
Background: The major burden of cervical cancer occurs in low- and middle-income countries. In Ghana, it is the second most common cancer among women. Infection with high-risk human papilloma virus (HPV) has been established as the cause of cervical cancer. As such, it is important to identify risk factors that may affect progression from HPV infection to cancer. Aims: We assessed the risk factors associated with cervical cancer in Ghana. Methods: To identify the risk factors for cervical cancer, we conducted an unmatched case–control study in two hospitals in Ghana where most cervical cancer cases are diagnosed. Women with histologically confirmed cervical cancer were the cases, whereas women without cancer seeking care at the two hospitals were controls. A structured questionnaire was administered to the women, after which cervical samples were sent for HPV deoxyribonucleic acid (DNA) testing. Results: Overall, 206 cases and 230 controls were recruited. After adjusting for possible confounders, women with the highest educational level had a significantly lower risk of cervical cancer than those with no or little formal education. Parity was a major risk factor (odd ratio [OR] for five or more children=7.9; 95% CI: 2.3–27.6), with risk increasing with increasing parity (p for trend <0.001). Women reporting the use of a homemade sanitary towel during menstruation also had an increased risk of cervical cancer compared with women who used a pad (OR: 7.3; 95% CI: 2.5–22.0). Conclusion: In this Ghanaian population, high parity and poor personal hygienic conditions were the main contributing factors to the risk of cervical cancer after adjustment for the presence of high-risk HPV genotypes.
Keywords: case–control; cervical cancer; cofactors; Ghana